Penguatan Branding melalui Sertifikasi Halal sebagai Strategi dalam Pemasaran Produk UMKM BKMT Kabupaten Kubu Raya - Suprihartini, Lia; Elida, Sri Syabanita; Wahyuarini, Tri; Listiyawati, Lilis; Wahyuni, Riska; Zulkifli; Habibie, Muhammad; Pranoto, Setya Aristu (Belalek, 2025)
Rasau Jaya is part of Kubu Raya Regency, located close to the administrative center of West Kalimantan Province. Economic growth in Kubu Raya Regency is also supported by Micro, Small, and Medium Enterprises (MSMEs), which serve as one of the key drivers of the local economy. One of the MSME groups with significant development potential is the group managed by the Badan Kontak Majelis Taklim (BKMT) of Kubu Raya Regency. Of the nine groups, four MSMEs previously obtained halal certification, but the certificates have expired. The remaining groups have not yet applied for certification due to limited access to information. As commonly understood, halal certification has become a necessity and can serve as a marketing strategy and product-branding development tool to support market expansion. The method used in this Community Service Program (PKM) involved conducting outreach and training sessions to provide information, enhance understanding, and explain the technical procedures for submitting halal certification applications. During the activities, participants demonstrated strong enthusiasm as they received more detailed and in-depth information about the concept and principles of halal, halal ingredients and production processes, identification of critical control points related to product halalness, understanding of halal regulations, and the processes and technical aspects involved in obtaining halal certification. Prior to the activity, participants were given a questionnaire to assess their general understanding of halal certification. After the outreach and training sessions were completed, they were given another questionnaire to measure changes in their understanding of halal and halal certification. The evaluation results indicate an improvement in participants’ comprehension and demonstrate the effectiveness of the PKM activity in achieving its objectives. This PKM activity is also expected to produce an academic article to be published in an ISSN-registered community service journal.